Development and validation of a quantitative electron microscopy score to assess acute cellular stress in the human exocrine pancreas. (22nd November 2020) - Kattner, Nicole; Dyson, Nicola; Bury, Yvonne; Tiniakos, Dina; White, Kathryn; Davey, Tracey; Eliasson, Lena; Tindale, Lynn; Wagner, Bart E; Honkanen‐Scott, Minna; Doyle, Jennifer; Ploeg, Rutger J; et al.
Abstract: The pancreas is particularly sensitive to acute cellular stress, but this has been difficult to evaluate using light microscopy. Pancreatic ischaemia associated with deceased organ donation negatively impacts whole‐organ and isolated‐islet transplantation outcomes. Post‐mortem changes have also hampered accurate interpretation of ante‐mortem pancreatic pathology. A rigorous histological scoring system accurately quantifying ischaemia is required to experimentally evaluate innovations in organ preservation and to increase rigour in clinical/research evaluation of underlying pancreatic pathology. We developed and validated an unbiased electron microscopy (EM) score of acute pancreatic exocrine cellular stress in deceased organ donor cohorts (development [ n = 28] and validation [ n = 16]). Standardised assessment led to clearly described numerical scores (0–3) for nuclear, mitochondrial and endoplasmic reticulum (ER) morphology and intracellular vacuolisation; with a maximum (worst) aggregate total score of 12. In the Validation cohort, a trend towards higher scores was observed for tail versus head regions (nucleus score following donation after brainstem death [DBD]: head 0.67 ± 0.19; tail 0.86 ± 0.11; p = 0.027) and donation after circulatory death (DCD) versus DBD (mitochondrial score: DCD (head + tail) 2.59 ± 0.16; DBD (head + tail) 2.38 ± 0.21; p = 0.004). Significant mitochondrial changes were seen ubiquitously even with short cold ischaemia, whereas nuclear and vacuolisation changes remained mild even after prolonged ischaemia. ER score correlated with cold ischaemia time (CIT) following DBD (pancreatic tail region: r = 0.796; p = 0.018). No relationships between CIT and EM scores were observed following DCD. In conclusion, we have developed and validated a novel EM score providing standardised quantitative assessment of subcellular ultrastructural morphology in pancreatic acinar cells. This provides a robust novel tool for gold standard measurement of acute cellular stress in studies evaluating surrogate measures of peri‐transplant ischaemia, organ preservation technologies and in samples obtained for detailed pathological examination of underlying pancreatic pathology.